2007
DOI: 10.1016/j.jhydrol.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alternative methodologies for identifying and characterizing preferential flow paths in heterogeneous aquifers

Abstract: International audienceOne of the main difficulties encountered when characterizing the hydrodynamic properties of a fractured aquifer is to identify the preferential flow paths within it. Different methods may be applied to determine the variability of the permeability at the borehole scale and to image the structure of the main flow zones between boreholes. In this paper, we compare the information obtained from different measurement techniques performed in a set of three 100 m depth wells (well-to-well spaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
107
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(118 citation statements)
references
References 31 publications
7
107
0
1
Order By: Relevance
“…From optical and acoustic televiewer logging, we observed that B1 crosses first a mica schist unit until z ≃−38 m, then a granitic unit. The contact between granite and the overlying mica schist is nearly horizontal in an area of ∼10 m around the boreholes (Figure ) [ Le Borgne et al , ]. Both rock formations exhibit strong fracturing as numerous open discontinuities are visible from the logs with a density attaining one fracture per meter along most of the borehole's length.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From optical and acoustic televiewer logging, we observed that B1 crosses first a mica schist unit until z ≃−38 m, then a granitic unit. The contact between granite and the overlying mica schist is nearly horizontal in an area of ∼10 m around the boreholes (Figure ) [ Le Borgne et al , ]. Both rock formations exhibit strong fracturing as numerous open discontinuities are visible from the logs with a density attaining one fracture per meter along most of the borehole's length.…”
Section: Methodsmentioning
confidence: 99%
“…The transmissivity at site scale is fairly high based on classical pumping tests ( T h =10 −3 m 2 /s [ Le Borgne et al , ]), but Klepikova et al [] calculated transmissivities of the fracture system ranging from 10 −6 to 10 −3 m 2 /s, which denotes a high degree of heterogeneity. In particular, the few permeable discontinuities intersecting B1 were found to be in the middle and lower transmissivity range of this interval ( Th2×104 m 2 /s).…”
Section: Methodsmentioning
confidence: 99%
“…They control the hydrodynamic properties of an aquifer as well as the transport of solutes and the dispersal of contaminants. Several methods can help determining the variability of permeability, or imaging the structure of the main flow zones in an aquifer around boreholes; these include geophysical and imaging logs, fluid logs-particularly temperature, conductivity and flow logs-as well as packer tests (Keys, 1990; Barton et al, 1995;Paillet and Pedler, 1996;Berkowitz, 2002;Schurch and Buckley, 2002;Maréchal et al, 2004;Kumar et al, 2007;Le Borgne et al, 2007;Chatelier et al, 2011;Dewandel et al, 2012). Whatever the geological context, the use of hydrochemical logging is less common, but has proved relevant for characterizing a heterogeneous aquifer (Schurch and Buckley, 2002;Schurch and Vuataz, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, geophysical methods can give information that is complementary to traditional characterization techniques such as direct observation of fractures, pumping tests and tracer experiments (e.g., [10][11][12]). Among the numerous existing geophysical approaches, electrical resistivity measurements are of particular interest because the effective electrical properties that they provide are sensitive to fluid content and can be obtained over a wide range of spatial scales.…”
Section: Introductionmentioning
confidence: 99%